Perbandingan Metode TOPSIS dan WASPAS dalam Penentuan Desa Terbaik di Kecamatan Setia Janji - Intan Febrianti; Sri Wahyuni; Siti Nurhalimah; Rabella Tidiwana Situmeang; Afrisawati Afrisawati (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
Every year, Setia Janji District routinely holds village competitions. Village competition assessments are held to motivate village officials and the community to compete in building a good village. As for the village assessment, currently the calculations in the assessment are still done manually and are not yet open. Assessments also still use paper so processing takes quite a long time and is sometimes unbalanced. By utilizing technological advances, a decision support system is needed to make it easier to determine the best village in Setia Janji District. The aim of this research is to determine the best village in Setia Janji District using a comparison of the TOPSIS Method and the WASPAS Method.